ANALISIS SISWA PUTUS SEKOLAH PADA JENJANG PENDIDIKAN SEKOLAH DASAR DI PESISIR LINGKUNGAN TANANGAN, KECAMATAN BANGGAE, KABUPATEN MAJENE, PROVINSI SULAWESI BARAT - Putri Amelia Dirham; Kaharuddin; Ashar (STKIP Subang, 2025)
Putri Amelia Dirham. 2025. An Analysis of School Dropout among ElementarySchool Students in the Coastal Area of Tanangan, Banggae District, MajeneRegency, West Sulawesi Province. Thesis. Department of Primary School TeacherEducation, Faculty of Teacher Training and Education, Muhammadiyah Universityof Makassar. Advisor I: Kaharuddin, S.Pd., M.Pd., Ph.D. Advisor II: Dr. Ashar, S.Or.,S.Pd., M.Pd. The main issue in this study is the persistent phenomenon of schooldropouts at the elementary education level, particularly in coastal areas such asTanangan, Banggae District, Majene Regency. This research aims to identify thefactors contributing to student dropouts and the efforts made to address thisproblem. This study uses a descriptive qualitative method. Data collectiontechniques include observation, interviews, and documentation. The informants inthis research consist of students’ parents, teachers, principals, and communityleaders. The results show that the causes of school dropouts are divided intointernal and external factors. Internal factors include lack of interest and motivationin learning, as well as health problems. External factors involve low family economicconditions, lack of parental attention and education, negative influences from thesurrounding environment, school-related factors, societal culture that prioritizeswork over education, and inflexible school policies regarding student violations.Efforts to reduce dropout rates include preventive and repressive approaches, andguidance from parents, schools, communities, and the government throughprograms such as educational scholarships. Based on these findings, it can beconcluded that reducing dropout rates in coastal areas requires collaboration amongvarious stakeholders and strategies that are aligned with the local social and culturalcontext.